'Envisioning Reform: A Revelation Of Purgatory and Anchoritic Compassioun in the Later Middle Ages' - Liz Herbert McAvoy (The Medieval Mystical Tradition in England Papers read at Charney Manor, July 2011 [Exeter Symposium 8], 2013)
This essay breaks new ground by examining a hitherto overlooked female-authored text from fifteenth-century Winchester, arguing for its need to be read alongside the writing of Julian of Norwich (d. c. 1416) and Margery Kempe (d. c. 1440) as an example of how a female-focused 'compassioun' imbricated the works of late-medieval women within late medieval England. The essay aims to demonstrate that such treatments by medieval women in their writing reflect a movement towards an ultimate feminisation of spiritual discourse that found fertile ground within the impetus for Church reform within the Lancastrian circles of fifteenth century England.